PENGEMBANGAN MULTIMEDIA WORDWALL UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK KALIMAT SPOK SISWA KELAS III SD - Santika, Dina; Marini, Arita; Yarmi, Gusti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and evaluate the effectiveness of Wordwall-based interactive multimedia in enhancing listening skills for Subject–Predicate–Object–Description (SPOK) sentence patterns among grade III elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 20 third-grade students from SDN Teluk Pucung I. Data were collected through pretest and posttest assessments, student response questionnaires, and expert validation sheets. Validation results indicated that the Wordwall media was classified as “very valid,” with scores of 95% from the material expert, 93.3% from the language expert, and 88.6% from the media expert. The media was implemented in classroom learning supported by a projector and involved quizzes and audio-based interactive listening activities. The N-Gain analysis showed an improvement of 0.46 (medium category). The paired sample t-test revealed a t-value of -10 with a p-value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. These findings demonstrate that the Wordwall media is effective in improving students’ listening skills, particularly in understanding SPOK sentence structures. This study recommends integrating interactive digital media into Indonesian language learning to create a more engaging, contextual, and meaningful learning experience.